The Role Of Educators In Reducing Radicalism And Extremism Among Islamic University Students In Malaysia - Siti Suriani Othman; Marina Munira Abdul Mutalib; Kartini Kamaruzzaman; Selvarani A/P P.Kovil Pillai (AID ACADEMY, 2024)
Radicalism and extremism are tendencies and activities that can affect people from all walks of life including university students. At the same time, Malaysia as an Islamic country is considered by the West as one of the countries that supports radicalism and extremism or has such tendencies. Thus, this study looks at the role of educators, especially lecturers in Islamic universities in Malaysia to reduce radicalism and extremism among students. This study conduct interviews with lecturers who teach Islamic courses in Malaysia to investigate how messages of de-radicalism are delivered in class at two universities namely Universiti Sains Islam Malaysia (USIM) and International Islamic University of Malaysia (IIUM). A total of six informants were interviewed to find out the status of radicalism and extremism at both universities. Secondly, this study also identifies teaching method or communication approach applied in class to examine the effectiveness to deliver anti radicalism and extremism messages. The study concludes that the status of radicalism and extremism among university students is not worrying in Malaysia, hence there is no specific teaching method applied in class to share messages related to radicalism and extremism in class. However, we have identified approaches of teaching and learning among lecturers who involve in de-radicalism and those who are not. Mainly, lecturers who involve in de-radicalism share their knowledge and experience in “mass form” in class, while lecturers who don’t, share the messages in a more individual or interpersonal approach. In conclusion, although the status of radicalism and extremism is low among students in Malaysia, hence there is no specific teaching and learning method on this matter. However, there is a specific difference in terms of approach used by lecturers involved in radicalism and those who don’t